2016
DOI: 10.1051/matecconf/20166600037
|View full text |Cite
|
Sign up to set email alerts
|

Local Authority Empowerment towards Quality Living Environment for Coastal Reclamation Area

Abstract: Abstract. Good urban governance administration system is the key to a successful physical planning development. A local authority of a local government concentrates on planning administration and executes the policies and strategies either the federal or state, or even the local's policies and strategies. Based on its characteristic as the lowest level of government, it becomes the best authority to regulate and monitor the development process within their territory. The significance of a local authority in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Schrage & Kjaeras emphasized that understanding local climate governance patterns may be an effective measurement to be considered a practical approach in governing low-carbon cities [33]. In addition, improving the management aspect may lead to the success of low-carbon city governance [34]. According to Figure 1 below, several criteria must be considered contributing to the changing of low-carbon governance.…”
Section: Administrative Of Low-carbon Citymentioning
confidence: 99%
See 2 more Smart Citations
“…Schrage & Kjaeras emphasized that understanding local climate governance patterns may be an effective measurement to be considered a practical approach in governing low-carbon cities [33]. In addition, improving the management aspect may lead to the success of low-carbon city governance [34]. According to Figure 1 below, several criteria must be considered contributing to the changing of low-carbon governance.…”
Section: Administrative Of Low-carbon Citymentioning
confidence: 99%
“…al, every local authority has its functions and responsibilities in achieving state targets. Thus to develop the best way to the administrative system of low-carbon cities, the local authority may improve one of the criteria to practice a better administration approach [34]. Source: Abdullah et al [35] The Federal Department of Town and County Planning governs urban development at the local level.…”
Section: Administrative Of Low-carbon Citymentioning
confidence: 99%
See 1 more Smart Citation
“…They believed that in the LCC approach, governance should pay attention to the process of LCC delivery, covering not only the management process but also the resources and planning. According to Yusup et al (2016), every local authority has its functions and responsibilities for achieving state targets. Because of that, to enhance the value of the administrative system for low-carbon cities, it is suggested that the local authority consider enhancing its administrative structure as one of the criteria for implementing a more effective administrative strategy (Yusup et al, 2016).…”
Section: 3mentioning
confidence: 99%
“…According to Yusup et al (2016), every local authority has its functions and responsibilities for achieving state targets. Because of that, to enhance the value of the administrative system for low-carbon cities, it is suggested that the local authority consider enhancing its administrative structure as one of the criteria for implementing a more effective administrative strategy (Yusup et al, 2016). According to Figure 5 below, Abdullah et al (2022a) have identified fourteen( 14) variables that can be adopted by the local authorities in governing the nation or city, including the guideline as the basis for the authorities, benchmarking the best practices, a system as the database, a zone to implement the suitable mechanism, the sources of funding, the collaboration between stakeholders, a champion who can derive the changes, key performance indicators to evaluate the performance in achieving the target, procurement that influences the minimal impact, especially toward the environment, monitoring approaches, a strategy included in the work plan, job description to highlight the scope of work, and finally the capacity building to empower the human resources.…”
Section: 3mentioning
confidence: 99%